Capture Cavities For The Cw Polarized Positron Source Ce+baf - Wang Shaoheng; Ushakov Andriy; Grames Joseph; Raut Nabin; Rimmer Robert; Roblin Yves; Wang Haipeng (EPJ Web of Conferences)
The initial design of the capture cavities for the continuous wave (CW) polarized positron beams at Jefferson Lab (Ce+BAF) is presented. A chain of standing wave multi-cell copper cavities inside a solenoid tunnel are selected to improve the positron capture efficiency. The cavity design strategy is presented to accommodate constrains from the large phase distribution of the incident beams, RF power and RF heating. A matrix of design parameters’ range are given for future system optimization when the capture cavities are considered together with other sub-systems and beam dynamics. The contents will also be useful for other CW cavity design for beams with large phase space distribution.